SISTEM PENGOLAHAN AIR LIMBAH DOMESTIK DAN TINJA DI IPAL JL JELAWAT SAMARINDA - Rahayu, Dwi Ermawati; Wijayanti, Dyah Wahyu (APLIKA Jurnal Ilmu Pengetahuan dan Teknologi, 2008)
Waste water treatment plant of Jelawat built as a part of "Prokasih" Karang Mumus river. Location of jelawat waste treatmant plant on sidomulyo and connected 6 RT in network pipe. Resources of waste water from domestic waste water like a kitchen, urinoir, presipitation and solid waste "excreta". Flow system of Jelawat waste water treatment plant are main pipe, manhole, persil pipe and CSD (Combine Sewer Drainage). In Jelawat waste water treatment plant are many unit treatment from pre treatment until final treatment. Step of unit treatment are bar screen, flotasi unit, primary clarifier, RBC (rotating Biological Contactor) and final clarifier. RBC is treatment by biological process used to microorganism culture attach in rotordisk. Quality of effluen jelawat waste water treatment plant is good to compare with SK Gubernur No.26/2002 about Standar Quality waste water for industries and comersial sources in East Kalimantan.